Pengaruh Variasi Menu dan Store Atmosphere terhadap Keunggulan Bersaing: Studi Kasus pada Warsun Cafe and Resto Bandung - Mohammad Alif Fazrin; Budi Wahyu Fitriadi; Ai Kusmiati Asyiah (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This study aims to determine the effect of menu variations and Store Atmosphere on competitive advantage (a consumer survey of Warsun Cafe and Resto Bandung). The method used in this study is causality through a survey approach. With a research sample of 100 consumers of Warsun Cafe and Resto Bandung. The data used is using primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results of the study show that Menu Variation and Store Atmosphere have a significant influence on Competitive Advantage at Warsun Cafe And Resto Bandung. Partially, Menu Variation has a significant influence on Competitive Advantage at Warsun Cafe And Resto Bandung. Partially Store Atmosphere has a significant influence on Competitive Advantage at Warsun Cafe And Resto Bandung.